Pengaruh Kualitas Pelayanan Dan Kinerja Karyawan Terhadap Kepuasan Nasabah Pada PT. BPR Artha Adyamurthi Di Kediri Tabanan - I Wayan Gede Antok Setiawan Jodi (Jurnal Ilmiah Satyagraha, 2018)
Rural Banks (BPR) are one type of bank that is known to serve customers, micro, small and medium enterprises. BPR is the official banking institution regulated in the Banking Law which functions not only to channel credit in the form of working capital, investment and consumption credit but also to collect public funds in the form of time deposits, savings and other forms equivalent to it. Based on this background, the title of this research is "The Effect of Service Quality and Employee Performance on Customer Satisfaction at PT. BPR Artha Adyamurthi in Kediri, Tabanan ". The formulation of the problem in this study is how the influence of service quality and employee performance simultaneously and partially on customer satisfaction at PT. BPR Artha Adyamurthi in Kediri, Tabanan. The purpose of this study is to analyze the effect of service quality and employee performance simultaneously and partially on customer satisfaction at PT. BPR Artha Adyamurthi in Kediri, Tabanan. The number of samples is 98 people. The analytical tools used in the study include classical assumption test, multiple linear regression, F test, and t test. From the results of the calculation of multiple linear regression analysis obtained the linear regression line equation between service quality and employee performance on customer satisfaction is Y = -1,710 + 0,296X1 + 0,765X2. Based on the F test results obtained Fcount value of 132.206 is greater than Ftable (3.07 then it is true there is a positive and significant effect between service quality and employee performance simultaneously on customer satisfaction at PT. BPR Artha Adyamurthi in Kediri, Tabanan. Results of analysis with using t-test, the t-count value of 2.695 and 10.085 is greater than the t-table value, the service quality and employee performance partially have a positive and significant effect between service quality and employee performance simultaneously on customer satisfaction at PT. BPR Artha Adyamurthi in Kediri, Tabanan.